EVALUATION OF THE ANTI-INFLAMMATORY ACTIVITY AND ULCEROGENIC LIABILITY OF 5-(3-CHLORO-1-BENZOTHIEN -2-YL)-4-PHENYL-4H-1,2,4-TRIAZOLE-3-THIOL - Mazin N. Mousa (Basrah Journal of Veterinary Research)
The aim of this study was to evaluate the anti-inflammatory and the ulcerogenic activity of 5-(3-chloro-1-benzothien -2-yl)-4-phenyl-4H-1,2,4-triazole-3-thiol. The anti-inflammatory effect of the compound was determined by comparing it with a standard drug (naproxen). The anti-inflammatory effects were studied by using carrageenan-induced paw edema method and Cotton pellet induced granuloma in rats and the ulcerogenic liability was assessed and compared with a standard drug. The results showed that the compound had an obvious anti-inflammatory effect and the activity is comparable to that of the standard drug with less ulcerogenic effects.